EFFECTIVE TECHNIQUES FOR TEACHING BASIC GRAMMAR - Ibayev Anvar Jurabekovich; Usarova Ruxshona Asqad qizi (TADQIQOTLAR, 2026)
Abstract: One of the biggest problems in language education is still teaching basic grammar well, especially at the beginning of the learning process. Grammar is the structure that lets people speak and write clearly and meaningfully in a language they don’t know. But traditional grammar lessons often focus too much on memorizing rules and doing mechanical exercises, which can make students less interested and less able to use the language in real life. Because of this, modern teaching methods stress the use of interactive, communicative, and learner-centered techniques that help students understand grammar in real-life situations. Teaching grammar well starts with showing grammatical forms in real-life language situations instead of just giving students rules. When students learn in context, they can see how grammar works in real-life situations. Teachers can teach grammar by using short conversations, stories, or real-life situations to show how certain structures are used. This method not only makes it easier for students to understand, but it also helps them remember forms better because they connect grammar to how language is actually used. Another good way to teach grammar is through inductive learning, where students figure out the rules by looking at examples instead of getting direct explanations first. Learners find patterns and connections between words in sentences through guided activities. This process helps people think critically and learn more about grammar.